Papier : Beeld & Basis : Utopia. - Van Den Abeele, Lieven; De Baere, Bart; De Smet, Eric; Gentils, Annie; Guestelle, M.; Hoet, Jan; Lambrecht, Luk; Peters, Philip; Schütz, Heinz; Van Nieuwenborgh, Gracienne; Vonck, Marc (Aalst : Stad Aalst, 1996)
Beuys, Joseph ; Van Buggenhout, Carl ; Daniels, René ; Dehais, Dominique ; Deleu, Luc ; Green, Renée ; Huber, Thomas ; Malevich, Kasimir ; Merz, Mario ; Mullican, Matt ; Neuhaus, Max ; Peters, Philip ; Peters, Ralf ; Pfannenmüller, Urs ; Schütte, Thomas ; Speekenbrink, Willem ; Van de Steeg, Niek ; Vercruysse, Jan ; Weiner, Lawrence ; Zalme, Marcel
Papier : Beeld & Basis : Utopia, Stad Aalst, 15/06/1996 - 18/09/1996
Nederlands
boek